2004
DOI: 10.1002/bdrb.20008
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity assessment of lasofoxifene, a selective estrogen receptor modulator (SERM), in male rats

Abstract: The changes in male fertility and reproductive tissue weights after exposure to lasofoxifene are consistent with those previously described for estrogen receptor-modulating compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
(79 reference statements)
2
2
0
Order By: Relevance
“…In both the cyclicity and the implantation studies, lasofoxifene reduced body weight, body weight gain, and food consumption. This was an expected finding based on observations from SERMs raloxifene (Hoyt et al, 1998;Clarke et al, 1998), tamoxifen (Tucker et al, 1984;Wallen et al, 2001), Mer-25 (Gray and Wade, 1981), and from lasofoxifene-treated males (Cappon et al, 2004). Lasofoxifene-induced reductions in food consumption and body weight are believed to be pharmacologically-mediated, with receptor saturation likely occurring at all doses.…”
Section: Discussionsupporting
confidence: 53%
“…In both the cyclicity and the implantation studies, lasofoxifene reduced body weight, body weight gain, and food consumption. This was an expected finding based on observations from SERMs raloxifene (Hoyt et al, 1998;Clarke et al, 1998), tamoxifen (Tucker et al, 1984;Wallen et al, 2001), Mer-25 (Gray and Wade, 1981), and from lasofoxifene-treated males (Cappon et al, 2004). Lasofoxifene-induced reductions in food consumption and body weight are believed to be pharmacologically-mediated, with receptor saturation likely occurring at all doses.…”
Section: Discussionsupporting
confidence: 53%
“…36 Also, there are studies in which any change of the testis and epididymis weights were not observed, while the reproductive toxic effects were shown to be induced. [37][38][39][40] According to our results, relative testis and epididymis weights did not change with ZNS administration. It can be stated that the reproductive toxic effect findings obtained with ZNS administration were not accompanied by the changes of the relative organ weights.…”
Section: Discussionsupporting
confidence: 45%
“…Clomiphene or tamoxifen have been the most used antiestrogen agents for the treatment of male infertility [138][139][140][141][142][143]; on the contrary the new generation of selective ER modulators does not show significant changes in male fertility [147,148]. Tamoxifen represents the first line treatment for men affected by idiopathic oligozoospermia as recommended by the World Health Organization (WHO) (2000) [137].…”
Section: Clinical and Therapeutical Implicationmentioning
confidence: 99%